T cell biology in neuromuscular disorders: a focus on Duchenne Muscular Dystrophy and Amyotrophic Lateral Sclerosis - Lemos, Julia Pereira; Tenório, Liliane Patrícia Gonçalves; Mouly, Vincent; Butler-Browne, Gillian; Mendes-da-Cruz, Daniella Arêas; Savino, Wilson; Smeriglio, Piera (Frontiers in Immunology, 2023)
Growing evidence demonstrates a continuous interaction between the immune system, the nerve and the muscle in neuromuscular disorders of different pathogenetic origins, such as Duchenne Muscular Dystrophy (DMD) and Amyotrophic Lateral Sclerosis (ALS), the focus of this review. Herein we highlight the complexity of the cellular and molecular interactions involving the immune system in neuromuscular disorders, as exemplified by DMD and ALS. We describe the distinct types of cellmediated interactions, such as cytokine/chemokine production as well as cell-matrix and cell-cell interactions between T lymphocytes and other immune cells, which target cells of the muscular or nervous tissues. Most of these interactions occur independently of exogenous pathogens, through ligand-receptor binding and subsequent signal transduction cascades, at distinct levels of specificity. Although this issue reveals the complexity of the system, it can also be envisioned as a window of Deleted: 1